2005
DOI: 10.1007/s11141-005-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

Sunset-sunrise characteristics of sporadic layers of ionization in the lower ionosphere observed by the method of resonance scattering of radio waves from artificial periodic inhomogeneities of the ionospheric plasma

Abstract: We present the results of studying the sporadic layers of ionization in the lower ionosphere observed in the sunset-sunrise time during the summer months of 2000 and 2001. Measurements were performed at the "Sura" heating facility of the Radiophysical Research Institute (Nizhny Novgorod, Russia). Based on the analysis of the altitude-time dependences of the amplitude, relaxation time, and phase of the scattered signal, we obtain new data on the formation and dynamics of the evening and nighttime mid-latitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 13 publications
1
28
0
1
Order By: Relevance
“…It was found that the number densities of atmospheric (NO + and O + 2 ) and metal ions depend on the altitude gradient dV/dh of the vertical velocity and the electron number density N s at the maximum of the E s layer. The estimates performed for June 15, 2001 yielded the number densities N m ∼ 7.3 · 10 3 −10 4 cm −3 and N a ∼ (5.3−8) · 10 4 cm −3 of metal and atmospheric ions, respectively, for sporadic layers at the altitudes h ∼ 100−113 km [6]. These values of the total number density of metal ions agree well with the results of lidar and rocket-based measurements.…”
Section: Study Of the Sporadic E Layersupporting
confidence: 80%
See 3 more Smart Citations
“…It was found that the number densities of atmospheric (NO + and O + 2 ) and metal ions depend on the altitude gradient dV/dh of the vertical velocity and the electron number density N s at the maximum of the E s layer. The estimates performed for June 15, 2001 yielded the number densities N m ∼ 7.3 · 10 3 −10 4 cm −3 and N a ∼ (5.3−8) · 10 4 cm −3 of metal and atmospheric ions, respectively, for sporadic layers at the altitudes h ∼ 100−113 km [6]. These values of the total number density of metal ions agree well with the results of lidar and rocket-based measurements.…”
Section: Study Of the Sporadic E Layersupporting
confidence: 80%
“…Within the framework of the concept that the mid-latitude sporadic E s layer is formed of long-lived metal ions, a method was proposed for determining the molecular mass of these ions, i.e., their sort and concentration, from the altitude dependence of the API relaxation time [6].…”
Section: Study Of the Sporadic E Layermentioning
confidence: 99%
See 2 more Smart Citations
“…The method of resonant scattering of radio waves by artificial periodic inhomogeneities of the ionospheric plasma, which was developed as a complex technique for diagnostics of the ionosphere and neutral atmosphere, has been used for a study of the inhomogeneous structure of the lower ionosphere and sporadic ionization layers for about a decade [1][2][3][4][5][6]. Artificial periodic inhomogeneities are formed in the field of a high-power standing radio wave resulting from the interference of the wave incident on and the wave reflected from the ionosphere.…”
Section: Introductionmentioning
confidence: 99%